Implementation of Smart TV As A Learning Medium to Support the Independent Learning Curriculum at Al Qur'an Tri Bhakti Attaqwa Middle School - Alfani, Ajeng Khori; Rosyid, Ahmad Sihabudin; Jaya, Arfin; Al Abror, M. Abdul Malik; Amri, Misbakhul; Jaenullah, Jaenullah (International Journal on Advanced Science, Education, and Religion, 2026)
The implementation of the Independent Curriculum (Curriculum Merdeka) is a form of educational transformation in Indonesia, emphasizing student-centered learning, strengthening competencies, and providing more space for teachers to develop innovative learning strategies. In its implementation, the Independent Curriculum requires the use of learning media that can create an active, creative, and enjoyable learning environment. The purpose of this study is to identify the use of smart TVs in supporting the Independent Curriculum, thus providing an overview of the implementation process, supporting factors, obstacles encountered, and its contribution to the implementation of learning in schools.This research method uses a qualitative approach with field research, aiming to deeply understand the implementation of smart TVs as a learning medium to support the independent learning curriculum at Al-Qur'an Tri Bhakti Attaqwa Middle School. This qualitative field research was chosen so that the researcher could directly visit the research location, observe, and understand the phenomena that occur naturally and contextually. The implementation of Smart TV as a learning medium to support the Independent Curriculum has been successful and has made a positive contribution to the learning process. Smart TVs can help teachers deliver material in a more engaging, interactive, and easily understood way for students. Although the school currently only has one Smart TV, its utilization can still be optimized through a well-organized system of alternating use between classes. Smart TVs have several advantages, including :Increased student activity during process learning, mens how that Smart TV is able to encourage student involvement in the learning process. However, in its implementation there are several obstacles faced. One of them isthe other one istendency to rely on the presentation of material via Smart TV. Thus, this study recommends various variations in learning methods by teachers and is able to make a good contribution to supporting and making the independent curriculum a success in an active, innovative and appropriate manner to the development of educational technology in Indonesia.